2021
DOI: 10.7554/elife.71513
|View full text |Cite
|
Sign up to set email alerts
|

Mutation saturation for fitness effects at human CpG sites

Abstract: Whole exome sequences have now been collected for millions of humans, with the related goals of identifying pathogenic mutations in patients and establishing reference repositories of data from unaffected individuals. As a result, we are approaching an important limit, in which datasets are large enough that, in the absence of natural selection, every highly mutable site will have experienced at least one mutation in the genealogical history of the sample. Here, we focus on CpG sites that are methylated in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 63 publications
6
29
0
Order By: Relevance
“…1c ). Synonymous mutations are often assumed to be unaffected by selection (neutral) 29 ; however, we found that synonymous CpG>TpG mutations are less saturated (85.7%) than those that are intergenic (89.9%), supporting the hypothesis that human codon usage is constrained 30 .…”
Section: Functionally Important Regionssupporting
confidence: 70%
See 1 more Smart Citation
“…1c ). Synonymous mutations are often assumed to be unaffected by selection (neutral) 29 ; however, we found that synonymous CpG>TpG mutations are less saturated (85.7%) than those that are intergenic (89.9%), supporting the hypothesis that human codon usage is constrained 30 .…”
Section: Functionally Important Regionssupporting
confidence: 70%
“…The extensive saturation of CpG>TpG variants at methylated CpGs in large WES cohorts has been used to identify genomic annotation or loci where their absence could be indicative of negative selection 21 , 29 . In line with previous reports 21 , we saw less saturation of stop-gain CpG>TpG variants than those that are synonymous (Fig.…”
Section: Functionally Important Regionsmentioning
confidence: 99%
“…1c). Synonymous mutations are often assumed to be unaffected by selection (neutral) 37 however we find that synonymous CpG>TpG mutations are less saturated (85.7%) than those that are intergenic (89.9%), supporting the hypothesis that human codon usage is constrained 38 .…”
Section: Resultssupporting
confidence: 63%
“…The extensive saturation of CpG>TpG variants at methylated CpGs in large WES cohorts has been used to identify genomic annotation or loci where their absence could be indicative of negative selection 11, 37 . In line with previous reports 11 we see less saturation of stop-gain CpG>TpG variants than those that are synonymous (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here again, the extent to which sites depleted of genetic variation reflects the presence of lethal mutations is not entirely clear. Demonstrating this, Agarwal and Przeworski (2021) used a similar approach by examining invariant methylated CpG sites in a sample of 390,000 human genomes, concluding that an additive mutation with a selection coefficient as small as s = 1 e − 3 is sufficient to result in a lack of variation even in the large sample sizes they used. Thus, approaches for detecting lethal mutations based on genetic variation data may have inherent limitations not only in disentangling s from h , but also in separating lethal mutations from mutations that are strongly deleterious though far from lethal ( s on the order of -0.001 to -0.1).…”
Section: Discussionmentioning
confidence: 99%